Pelatihan SEO untuk Pembuatan Artikel Informasi di Proklim RW 11 Pekayon Jaya Bekasi - Agus Hermanto; Tria Patrianti; Sa’diyah El Adawiyah; Indriyani Idris; Laila Yumna; Rahma Dayanti (Jurnal Surya Masyarakat, 2026)
This community service activity was carried out at the Proklim RW 11 Pekayon Jaya Bekasi City. The activities carried out were related to SEO, as one way to create informative articles using digital technology that is more structured, systematic and massive and adapted to current media developments, especially the digital or online world. The purpose of this activity was to further concentrate the participants' (Proklim members) basic knowledge and skills in SEO techniques in creating informative articles. The method used was service-learning in the training with four stages: preparation, planning, implementation, and closing. The one-day activity took place conducively with a positive response from the participants. The community service training activities were carried out according to the structure and objectives as well as the technical plan that had been designed. The majority of participants (90% strongly agree) greatly benefited from the increased knowledge about search engines and keywords on Google in relation to SEO. Understanding also (90% strongly agree) increased in search engine applications by using keywords to support the creation of informative articles that have content visibility and are adaptive and synergistic with the development of issues in the internet-based digital realm.